Effectiveness of Tax Sanctions and Examination of Taxpayers On Taxpayer Compliance With Quality of Service as Moderating Variable : Efektivitas Sanksi Pajak dan Pemeriksaan Pajak Terhadap Kepatuhan Wajib Pajak Dengan Kualitas Pelayanan Sebagai variabel Moderasi - Ayu Windasari; Herman Ernandi (Academia Open, 2021)
This study aims to determine the effectiveness of tax sanctions and taxpayer audits on taxpayer compliance with service quality as a moderating variable. The analytical tool used is tabulating the questionnaire, collecting data in the form of validity testing and reliability testing. The hypothesis in this study is that there is an effect of tax sanctions and tax audits on taxpayer compliance with service quality as a moderating variable. Testing this hypothesis using the SmartPLS analysis tool. The results obtained based on the validity test showed that all statements on the questionnaire were declared valid. To test the reliability test of all variables obtained from Composite Realibility or Cronbach's Alpha value is declared realible. And for hypothesis testing based on R-Square and T-statistics, it shows that not all hypotheses are accepted. The result of the hypothesis states that Tax Audit has an effect on taxpayer compliance. And there is no effect between tax sanctions on taxpayer compliance, tax sanctions on taxpayer compliance moderated by service quality, and tax audits moderated by service quality.